Perancangan Implementasi Aplikasi EduFund untuk Crowdfunding Pendidikan Mahasiswa dengan Keamanan Data Terintegrasi - Zihan Adin Fisabilillah; Ihsan Nurdin; Nayla Salsabila; Aigha Soraya Akmal; Deden Pradeka; Zahra Khaerunnisa (Jurnal IT UHB, 2026)
This study proposes a mobile-based educational crowdfunding application to support students facing financial difficulties, in line with Sustainable Development Goal (SDG) 4. The primary challenge in digital donation platforms is vulnerability to transaction manipulation and falsification of verification documents. The “EduFund” application was developed using the Flutter framework with a client-server architecture, utilizing Firebase (Auth and Firestore) and Cloudinary on the backend. This study proposes the integration of a layered security approach (Defense in Depth) encompassing three protection layers: (1) token-based authentication with Role-Based Access Control (RBAC), (2) financial transaction integrity using a digital signature (SHA-256) generated using the user’s private key, and (3) document authenticity verification using steganography with the EOF Injection method. Functional and security testing results demonstrate that the digital signature mechanism successfully validates data integrity during fund withdrawals and detects data-tampering attempts, with an average signature generation time of 1.04 ms. Meanwhile, the steganography technique successfully embeds user metadata into proof documents within an execution time range of 6.80–30.10 ms without introducing observable visual distortion, enabling digital forensic verification of donation document authenticity.